Pengaruh konsumsi cookies garut (Marantha arundinacea) yang mengandung glukomanan porang sebagai makanan selingan terhadap kadar kolesterol total penyandang diabetes mellitus tipe 2 - Frida Rahmawati; Eni Harmayani; Vita Yanti Anggraeni; Lily Arsanti Lestari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Effect of consuming arrowroot cookies containing glucomannan porang as a snack on total cholesterol levels of people with type 2 diabetesBackground: People with type 2 diabetes (T2D) have a risk of dyslipidemia, which is an increase in total cholesterol levels. Dietary fiber is known to have health benefits for improving lipid profiles. Arrowroot cookies containing glucomannan porang is a snack with high dietary fiber content.Objective: This study aims to determine the effect of consuming arrowroot cookies as a snack for 8 weeks on the total cholesterol levels of people with type 2 diabetes.Methods: This study is a quasi-experimental study with a pre-test post-test design with control group. Subjects are type 2 diabetes patients who are registered in four Yogyakarta City Health Centers. The intervention group was given five arrowroot cookies (65 grams) as a substitute snack for 8 weeks. Arrowroot cookies contain 0.57% soluble fiber and 15.80% insoluble fiber. Fasting total cholesterol levels, nutrient intake, anthropometry, and physical activity were measured twice, at pre- (week 0) and post-intervention (8th week).Results: The average total cholesterol levels of the control group and intervention group changed with no significant difference between the two study groups. The intervention group experienced a significant increase in total cholesterol levels (p<0.05) from 182.36 mg/dL to 202.55 mg/dL. There were no significant changes in anthropometric and physical activity. There was an increase in fiber intake in both groups but it was not significant for the intervention group (p=0.051).Conclusion: There was a significant change in the total cholesterol level of people with type 2 diabetes after consuming arrowroot cookies containing glucomannan porang as a snack for 8 weeks.